Common Organisms causing surgical site infection(SSI) in Postoperative patients in a tertiary care Hospital - Fatima Mustafa; Mumtaz Ahmed Khan; Abdullah Mustafa; Arifa Manzoor; Safia Safa; Samiullah Khogyani (Journal of Rawalpindi Medical College)
Objective: